From Digital Natives to Agile Learners: Rethinking Digital Skills among Generation Z - Hendrawan, Koen; Mardi; Susita, Dewi (Program Studi S3 Ilmu Manajemen, 2024)
This study explores the digital skills of Generation Z students through a qualitative lens, emphasizing the concept of agile digital skills as a multidimensional and adaptive competence. Drawing on in-depth interviews and focus group discussions with university students, the research investigates how young people understand, apply, and evaluate digital technologies in their academic and personal lives. The findings indicate that while students demonstrate strong operational proficiency with popular applications, they face significant challenges in theoretical knowledge and evaluative competences, particularly in critical assessment of online information. Moreover, social factors such as family background, gender, and prior learning experiences significantly shape the development of digital skills. By situating these findings within the frameworks of the second level digital divide and digital literacy theory, the study highlights the importance of cultivating agility in digital competence that is, the ability to adapt, transfer, and critically apply digital skills across diverse contexts. For higher education, this underscores the urgent need for curricula that integrate technical, conceptual, and evaluative components to promote critical digital citizenship, employability, and lifelong learning. Ultimately, digital literacy must be reframed not as a static skill set but as an evolving capacity for resilience and adaptation in the rapidly changing digital economy.